Pulmonary artery banding in the current era: Is it still useful? - Maziar Gholampour Dehaki; Ali Sadeghpour Tabaee; Changiz Azadi Ahmadabadi; Alireza Alizadeh Ghavidel; Gholamreza Omra (Wolters Kluwer Medknow Publications, 2012)
Background: The objective of this study was to assess the results of the pulmonary artery (PA) banding in patients with congenital heart defects (CHD) and pulmonary hypertension (PH) in the current era. Methods: We analyzed data from 305 patients who underwent PA banding between April 2005 and April 2010 at our centre. All patients were approached through a left thoracotomy. Twenty percent of patients underwent PA banding based on Trusler's rule (Group 1), 55% of them underwent PA banding based on PA pressure measurement (Group 2), and the rest of them (25%) based on surgeon experience (Group 3). The follow-up period was 39 ± 20 month and 75% of patients (230 cases) had definitive repair at mean interval 23 ± 10 months. Results: The rate of anatomically and functionally effectiveness of PA banding in all groups was high (97% and 92%, respectively). There were no significant differences in anatomically and functionally efficacy rate between all groups (P=0.77, P=0.728, respectively). There was PA bifurcation stenosis in six cases (2%), and pulmonary valve injury in one case (0.3%). The mortality rate in PA banding was 2% and in definitive repair was 3%. Conclusions:We believe that PA banding still plays a role in management of patients with CHD, particularly for infants with medical problems such as sepsis, low body weight, intracranial hemorrhage and associated non cardiac anomalies. PA banding can be done safely with low morbidity and mortality.